Monoterpenyl Glycosyltransferases Differentially Contribute to Production of Monoterpenyl Glycosides in Two Aromatic Vitis vinifera Varieties - Li, Xiang-Yi; Wen, Ya-Qin; Meng, Nan; Qian, Xu; Pan, Qiu-Hong (Frontiers in Plant Science, 2017)
HIGHLIGHTS A similar trend on accumulation of glycosidically bound monoterpenes was observed in both varieties Two VvGT7 alleles mutations occurred at key sites in Muscat blanc à Petit VvGT14 exerted a major role in production of monoterpenyl glycosides in both varieties Terpenoids are the major aroma components and generally exist as both free and glycosidically-bound forms, of which nonvolatile glycosides account for a large fraction in grape berries. Our previous study has indicated that differential accumulation of monoterpenyl glycosides in Vitis vinifera “Muscat blanc à Petit” between two regions is closely correlated to monoterpenyl glucosyltransferase (VvGT14, XM_002285734.2) transcript abundance. However, it has not been determined yet whether this correlation also exists in other Vitis vinifera varieties. This study investigated the evolution of free and glycosidically bound monoterpenes in two Vitis vinifera variety “Muscat blanc à Petit” and “Gewurztraminer” under two vintages, and further assessed the relation between the accumulation of bound monoterpenes and two monoterpenyl glycosyltransferase transcript levels. Results showed that free monoterpenes exhibited three evolution patterns in both varieties during berry development of two vintages, whereas glycosidically bound monoterpenes showed a concentration elevation with berry maturation. The Cis-rose oxide and geraniol were major components contributing to the aroma odors of “Gewürztraminer” grapes while linalool was major aroma contributor to the “Muscat blanc à Petit grain” grapes. The accumulation of glycosidically bound monoterpenes in both varieties was accompanied with the high expression of VvGT7 (XM_002276510.2) and VvGT14. Only one allele of VvGT7 was found in the variety “Gewürztraminer” and no mutation was observed in its enzyme active sites. XB-VvGT7-4 and XB-VvGT7-5 were two alleles of VvGT7 detected in “Muscat blanc à Petit grain.” The mutation on its enzyme active site inhibited the activity of XB-VvGT7-4, whereas VvGT7-5 exhibited an alteration on enzyme activity due to the insertion mutation at the position 443. Only one VvGT14 allele was found in both varieties, and the VvGT14 allele in both varieties showed the similarity on amino acid sequence. No mutation occurred in active sites of VvGT14 allele. These indicated that VvGT7 and VvGT14 differentially contributed to the production of monoterpenyl glycosides in these Vitis Vinifera varieties.